2015
DOI: 10.5851/kosfa.2015.35.4.486
|View full text |Cite
|
Sign up to set email alerts
|

Texture Softening of Beef and Chicken by Enzyme Injection Process

Abstract: This research focuses on a new softening technology for use with chicken breast and eye of round beef in order to assist elderly individuals who have difficulty with eating due to changes in their ability to chew (masticatory function) or swallow. We investigated the hardness of chicken breast and eye of round beef through use of a texture analyzer after injection of a commercial enzyme. Among 7 commercial enzymes, bromelain and collupulin exhibited a marked softening effect on the tested chicken breast and ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This was followed by bromelain and ficin treatments which decreased the hardness by about 14% and 10%, respectively, compared to the control on day 0 of storage. Bromelain was also reported to decrease the hardness values in chicken breast (Eom et al 2015). Rawdkuen et al (2013) found that the firmness and toughness values significantly decreased in pork, beef and chicken when treated with proteolytic extract from Calotropis procera latex.…”
Section: Effect Of Different Enzyme Treatments On Textural Propertiesmentioning
confidence: 96%
“…This was followed by bromelain and ficin treatments which decreased the hardness by about 14% and 10%, respectively, compared to the control on day 0 of storage. Bromelain was also reported to decrease the hardness values in chicken breast (Eom et al 2015). Rawdkuen et al (2013) found that the firmness and toughness values significantly decreased in pork, beef and chicken when treated with proteolytic extract from Calotropis procera latex.…”
Section: Effect Of Different Enzyme Treatments On Textural Propertiesmentioning
confidence: 96%
“…The third hardness level (under 2 × 10 4 N/m 2 and viscosity over 1500 mPa·s) refers to foods that can be broken up by tongue. Finally, the fourth hardness level (under 5 × 10 3 N/m 2 and viscosity over 1500 mPa⋅s) refers to foods that do not require chewing (Eom, Lee, Chun, Kim, & Park, ; Park et al., ). These levels are used here to evaluate the texture of foods treated with selected processing technologies.…”
Section: Dysphagiamentioning
confidence: 99%
“…Under 5 × 10 3 -->1500 10 3 N/m 2 and viscosity over 1500 mPas) refers to foods that do not require chewing (Eom, Lee, Chun, Kim, & Park, 2015;Park et al, 2017). These levels are used here to evaluate the texture of foods treated with selected processing technologies.…”
Section: Desired Characteristics Of Dysphagia Foodsmentioning
confidence: 99%
“…Other thawed squid strips were injected with the two aforementioned enzymes at a dosage of 1 mL of 0.1%, 0.2%, or 0.3% papain or bromelain solution per 10 g of mantle (six experimental treatments altogether), the solution being delivered perpendicular to the plane of the strip at sites approximately 1 cm apart. Injected and control samples were kept for 24 h at 4 • C [16]. Orbital shaking in vacuum was carried out using a vacuum desiccator (P14-1000240, Hondwen Co. Ltd, Taipei, Taiwan) with a polycarbonate top and polypropylene bottom enclosing a cylindrical chamber 240 mm wide and 311 mm deep, placed atop an orbital shaker (MS-NOR 30, Major Science, Saratoga, CA, USA).…”
Section: Experimental Squid Samplesmentioning
confidence: 99%
“…The compressive force rises with sample hardness. Tests were performed with three replicates of each sample centered under the probe [16].…”
Section: Texture Analysismentioning
confidence: 99%